Hybrid warfare and public health: Conflicts in Ukraine and Nagorno-Karabakh raise the alarm - Katherine Kricorian; Kaveh Khoshnood; Sharon Chekijian (Elsevier, 2022)
Hybrid warfare strategies include weaponization of healthcare, the use of non-conventional weapons, and strategic displacement of civilian populations via direct targeting, sexual violence, disinformation campaigns, and disruption of essential services such as water, food, gas, and access to health services. All these actions harm public health. The current war in Ukraine and the 2020 Second Nagorno-Karabakh war between Azerbaijan and Armenia serve as vivid examples of the novel and devastating public health effects of hybrid warfare targeting civilians. The lessons learned from these conflicts should serve as a warning and a call to action. Politicians and public health officials should advocate for a comprehensive rethinking of previous measures to counteract the impacts of hybrid warfare. Concerted efforts and strategies to mitigate these impacts on public health at every phase are essential. De-escalation of conflicts should be facilitated, and civilian health should be prioritized by the global community by instituting a more punitive and comprehensive schema to both deter war and step-up penalties for the tactics of hybrid warfare. Failure to do so will undoubtedly result in this scenario being played out with greater frequency globally, erasing the public health wins of the previous century.